Studi Kritis atas Transmisi dan Otoritas Keagamaan di Media Sosial - Muhtador, Moh (FIKRAH, 2018)
The development of social media raises a problem related to social change authorities such as thinking paradigms, social behavior, and religious models. This article aims to criticize the development of religious teachings found on social media. The method used is descriptive-critical by using the authority theory Abou El Fadl to assess and analyze the development of religious models in social media while transmission theory to find the authenticity of religious teachings. The result is known that the development of religious models on social media does not display scientific transmission. Religious developments that exist in social media tend to be textual-dogmatic in style, thus impacting on a stagnant religious attitude. The importance of this article is to provide a critical review of the development of religious knowledge found on social media. The critical study lies in the aspect of substance (material) or aspects of transmission (narrator). The authenticity and the development of religious teachings on social media can be known.